Cyclostephanos salsae and Placoneis patagonica, two new diatoms (Bacillariophyta) from Laguna Cháltel in southern Patagonia, Argentina - Maidana, Nora Irene (2018)
Two new diatom species, Cyclostephanos salsae and Placoneis patagonica found in plankton, superfi cial sediments and quaternary lacustrine sediment samples from Laguna Cháltel, Southern Argentina, are described. The detailed morphology of these two taxa is examined using both light (LM) and scanning electron microscopy (SEM). The main morphological features that distinguish C. salsae sp. nov. are the raised central area without fultoportulae and with scattered areolae, and the presence of some interstriae bifurcated on the valve mantle, bearing one fultoportulae in one of the forks. The variable, sometimes asymmetrical outline and the irregularly spaced central striae are the main morphological features of P. patagonica sp. nov. The relationships of these two new taxa with morphologically similar species and their ecological affi nities are discussed.